Orientalism and Challenges to Islamic Sources - Firdaus Ulul Absor (مجلة النور الدولية للقرآن والحديث, 2024)
This study investigates the socio-cultural roots of orientalist perspectives and their impact on the study of Islam and the Eastern world. Employing a qualitative approach, the research draws from the works of key orientalists such as Joseph Schacht, Arent Jan Wensinck, and Ignaz Goldziher, alongside critical analyses from scholars like Edward Said and Muṣṭafa al-Sibaʻī. The research examines how excessive ethnocentrism and cultural ʻaṣabiyyah (group solidarity) have historically influenced Orientalist views and actions, including the propagation of tendentious and discriminatory claims about the Eastern world and Islam. The study utilizes content analysis and critical discourse analysis to uncover the underlying ideologies and power relations within orientalist discourse. The findings reveal that the orientalist tradition of casting doubts on Islamic sources, such as the Sunnah, is rooted in a deeply ingrained cultural ʻaṣabiyyah and a desire to assert Western cultural and intellectual dominance. By understanding these socio-cultural factors, this study aims to provide a framework for anticipating and countering the challenges posed by orientalist ethnocentrism and cultural dominance.